Perfusion process combining low temperature and valeric acid for enhanced recombinant factor VIII production. (22nd October 2019) - Coronel, Juliana; Heinrich, Christoph; Klausing, Sandra; Noll, Thomas; Figueredo‐Cardero, Alvio; Castilho, Leda R.
Abstract: Perfusion operation mode remains the preferred platform for production of labile biopharmaceuticals (e.g., blood factors) and is also being increasingly adopted for production of stable products (e.g., monoclonal antibodies). Regardless of the product, process development typically aims at maximizing production capacity. In this work, we investigated the impact of perfusion cultivation conditions on process productivity for production of human factor VIII (FVIII). Recombinant CHO cells were cultivated in bioreactors coupled to inclined settlers and the effects of reducing the temperature to 31°C with or without valeric acid (VA) supplementation were evaluated. Increases in cell specific productivity (qp ) up to 2.4‐fold (FVIII concentration) and up to 3.0‐fold (FVIII biological activity) were obtained at 31°C with VA compared to the control at 37°C. Biological activity is the most important quality attribute for FVIII and was positively affected by mild hypothermia in combination with the chemical inducer. The low temperature conditions resulted in enhanced product transcript levels, suggesting that the higher qp is related to the increased mRNA levels. Furthermore, a high‐producer subclone was evaluated under the perfusion conditions optimized for the parental clone (31°C with VA), yielding increases in qp of 6‐fold and 15‐fold compared to the parental clone cultivated under the same condition and at 37°C, respectively. The proposed perfusion strategy enables increased product formation without increasing production costs, being potentially applicable to perfusion production of other CHO‐derived biopharmaceuticals. To the best of our knowledge, this is the first report showing the benefits of perfusion combining mild hypothermia with VA supplementation.